THE PROBLEMS THAT ARISE IN THE FORMATION OF STUDENTS' WRITING SKILLS IN ENGLISH - Ermatova Dilafruz Yodgorjon qizi; Xabibullayeva Zarina Zaribjon qizi; Ahmedova Matluba Ibragimjonovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2023)
Annotation: Developing strong writing skills in English is crucial for students as it empowers them to effectively express their thoughts and ideas. However, the process of attaining proficiency in writing can be challenging, particularly for non-native English speakers. This article aims to shed light on the common problems faced by students in their journey towards mastering writing skills in English and provides some suggestions to address these challenges.